2014
DOI: 10.1007/978-3-319-10479-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ethylene Diurea-Induced Protection in Plants Against Ozone Phytotoxicity

Abstract: Urbanization, industrialization and unsustainable utilization of natural resources have made tropospheric ozone (03) one of the world's most significant air pollutants. Past studies reveal that 0 3 is a phytotoxic air pollutant that causes or enhances food insecurity across the globe. Plant sensitivity, tolerance and resistance to 0 3 involve a wide array of responses that range from growth to the physiological, biochemical and molecular. Although plants have an array of defense systems to combat oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 187 publications
(178 reference statements)
1
31
0
Order By: Relevance
“…The harvest was done at the end of the growing season when plants stopped producing new leaves and, therefore, cannot be proved if plants treated with spray of 200 and 400 mg EDU L -1 compensated the accelerated leaf senescence by producing more leaves during the growing season (Kolb and Matyssek 2001). The reviews by Paoletti et al (2009) and Singh et al (2015) suggested that EDU delays the O 3 -induced accelerated senescence and this coincides with the findings of the present study. However, the fact that EDU soil drench protected against EOZ-induced accelerated senescence while did not protect against EOZ damage to all the other response variables (which are not related to the leaf number) indicates that either the EDU mode of action in protecting against O 3 injury is not upon protecting against O 3 -accelerated senescence -which is in agreement with suggestions by Eckardt and Pell (1996)-or EDU protection against EOZ injury was not completeas reported also by Paoletti et al (2007).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The harvest was done at the end of the growing season when plants stopped producing new leaves and, therefore, cannot be proved if plants treated with spray of 200 and 400 mg EDU L -1 compensated the accelerated leaf senescence by producing more leaves during the growing season (Kolb and Matyssek 2001). The reviews by Paoletti et al (2009) and Singh et al (2015) suggested that EDU delays the O 3 -induced accelerated senescence and this coincides with the findings of the present study. However, the fact that EDU soil drench protected against EOZ-induced accelerated senescence while did not protect against EOZ damage to all the other response variables (which are not related to the leaf number) indicates that either the EDU mode of action in protecting against O 3 injury is not upon protecting against O 3 -accelerated senescence -which is in agreement with suggestions by Eckardt and Pell (1996)-or EDU protection against EOZ injury was not completeas reported also by Paoletti et al (2007).…”
Section: Discussionsupporting
confidence: 64%
“…200-400 mg L -1 (Paoletti et al 2009, Feng et al 2010. EDU has been studied as a protectant of plants against O 3 , as an O 3 biomonitoring tool or as a comparative tool for screening other chemicals as to their efficacy to protect plants against O 3 impact (Paoletti et al 2009;Feng et al 2010;Manning et al 2011;Agathokleous et al 2015b;Singh et al 2015). EDU has been applied to plenty of agricultural crops.…”
Section: Introductionmentioning
confidence: 99%
“…More than 100 research articles about EDU role in plants exist in Science Citation Index (Thomson Reuters Co., New York). The mechanism through which EDU protects plants against O 3 injury has not been elucidated yet (Agathokleous, 2017;Agathokleous et al, 2015;Manning et al, 2011a;Oksanen et al, 2013;Paoletti et al, 2009;Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unknown if EDU high doses would contribute with N and cause toxicity when the plants have relatively large leaf area and the soil does not lack N, and this is an important issue (Agathokleous et al, 2015;Manning et al, 2011b;Singh et al, 2015). One important aspect is that EDU amounts in soil may vary over time, when EDU is applied as soil drench, because EDU may be adsorbed onto soil organic matter and released gradually through resolubilization by irrigation water, thereby potentially leading to greater amounts in the soil than the applied ones at random times (Pasqualini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is a prevalent indication that EDU does not modify the stomatal conductance of plants in comparison with non-EDU treatment, suggesting that antiozonant activity of EDU is biochemical rather than biophysical in nature (Feng et al 2010), but conclusive proof of the intimate bases for the protective action remains elusive, and the mode of action of EDU remains disputed or unconfirmed. However-whatever its mode of action-EDU is a reliable, low-cost, and low-technology efficient tool for assessing O 3 effects on plant performances in the field, when EDU-treated and EDUuntreated individuals are exposed to ambient air in the presence of O 3 (Singh et al 2014). This is the first report dealing with EDU applications to olive trees (Feng et al 2010), and the main objective of this study was to evaluate the use of EDU as a possible, efficient, cost-effective tool to estimate O 3 effects on olive plants (Olea europaea L. cultivar Kalamata) under field conditions in an area subjected to relevant ambient O 3 pressure.…”
Section: Introductionmentioning
confidence: 99%